Badaloni, Laura; Ferroviarios del Central Argentino. La conformación de un colectivo de trabajadores (1902-1933); Imago Mundi / CEHTI, Buenos Aires, 2022, 422 pp - Spagnoli, Micaela (2022)
Fil: Spagnoli, Micaela